Induction of periodontitis and oral microbiome dysbiosis in a mouse model with heart failure with preserved ejection fraction results in worsening hypertension and diastolic dysfunction. (3rd October 2022) - Da'na, S; Abedat, S; Nachman, D; Rokach, Y; Qadan, A; Karram, S; Tzach-Nahman, R; Beeri, R; Amir, O; Houri-Haddad, Y; Asleh, R
Abstract: Introduction: Heart Failure with Preserved Ejection Fraction (HFpEF) is characterized by increased inflammation and disruption of the nitric oxide (NO) pathway. Oral microbiota has an essential role in the generation of a large portion of the NO bioavailability pool in the human body. Periodontitis (PD) is a common inflammatory condition that contributes to the development of chronic low-grade inflammation, oral microbiota dysbiosis, and dysregulation of the NO hemostasis. Purpose: In this study, we sought to investigate the direct effect of PD induction on HFpEF manifestation in a mouse model. Methods: HFpEF was induced in 11-week-old C57/black male mice by high-fat diet and inhibition of NO synthase using L-NAME (Nω-nitro-l-arginine-methyl-ester) (a "2-hit-model") for 10 weeks. PD was induced by oral infection with P. gingivalis. Diastolic function of the left ventricle (LV) was assessed by high-frequency echocardiography. Blood pressure (BP) was measured using CODA non-invasive tail-cuff system. Results: Induction of PD resulted in a significantly impaired diastolic function demonstrated by more pronounced decrease in e' and increase in E/e' ratio compared to HFpEF without PD or control mice (E/e': 39.7±2.6 vs. 30.1±1.9 vs. 24.3±2.1 for PD-HFpEF [n=15], HFpEF [n=15], and controls [n=10], respectively, p<0.001). While LV ejection fraction (EF) was similar, global longitudinal strain (GLS) was decreased in the HFpEF group and further decreased in the PD-HFpEF group compared to controls (p<0.001). BP was elevated in the HFpEF mice and PD induction resulted in a more remarkable increase in BP (systolic BP: 124.7±3.3 vs. 112.7±3.8 vs. 94.8±2.2 mmHg, respectively, p<0.001). Conclusions: Induction of PD in a mouse model with HFpEF results in a more pronounced BP elevation and diastolic dysfunction compared to HFpEF without PD. Extensive molecular experiments are ongoing to explore the mechanisms responsible for the increased HFpEF severity in the setting of PD. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Israel Science Foundation